Functional Evaluation of Fracture Shaft of Femur Treated by Antegrade Closed Interlocking Nail at B.P. Koirala Institute of Health Sciences, Dharan - Gupta, Pradeep Kumar; Basnet, Ramesh; Shrestha, Niraj Man (Birat Journal of Health Sciences, 2018)
Introduction: The management of fractures of the femoral diaphysis has changed considerably in the last 30 years. Since the advent and popularization of intramedullary nailing the treatment of fracture shaft of femur has become a good, safe and reproducible procedure for the successful management of fracture shaft of femur. Objective: The objective of the study was to assess the various postoperative outcomes of the interlocking nail of fracture shaft of femur. Methodology: This study was prospective cohort study conducted at B.P. Koirala Institute of Health Sciences, Dharan from March 2002 to Feb 2004. Seventy five consecutive patients, having fractures shaft of femur were treated by anterograde closed interlocking nail. Data analysis was done by using EpiInfo 2000 software. Results: The most common cause of fractures shaft of femur was road traffic accident (69.3%). The average union time was 14.9 ± 1.3 weeks. There was wound infection in four cases superficial infection in open grade II but no deep infection. There was two cases of pudendal nerve palsy which recovered within 4 months. There were 5 cases of broken interlocking distal screw and 4 cases had more than 1.5 cm shortening of femur Conclusions: The antegrade reamed femoral nailing provides excellent results in management of fractures shaft of femur. Birat Journal of Health Sciences Vol.2/No.3/Issue 4/Sep- Dec 2017, Page: 244-247